Cell Interaction - Molecular and Immunological Basis for Disease Management 2021
DOI: 10.5772/intechopen.95551
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dendritic Cells in Pathogen Infections: A Current Perspective

Abstract: Dendritic cells (DC) represent an important link between innate and adaptive immunity, which play an important role during the immune response against pathogens. There are several populations and subpopulations of DC, but mainly two subpopulations are characterized: the classic DC specialized in the processing and presentation of the antigen; and the plasmacytoid DC that have a high phagocytic activity and capacity for the production of cytokines. This chapter aims to present the current aspects related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 146 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…Through the process of acquiring, processing, and presenting pathogen-specific antigens in times of infection by human pathogens (viruses, bacteria, etc. ), DCs induce the activation and differentiation of naïve T cells and, consequently, induce pathogen-specific T cell responses to activate host defense against pathogens [ 35 , 36 ]. However, excessive induction of DC maturation leads to excessive cytokine secretion, resulting in the stimulation of normal cells, induction of cell apoptosis, and secondary stimulation of immune cells by dead cells, ultimately causing acute or chronic inflammatory diseases [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the process of acquiring, processing, and presenting pathogen-specific antigens in times of infection by human pathogens (viruses, bacteria, etc. ), DCs induce the activation and differentiation of naïve T cells and, consequently, induce pathogen-specific T cell responses to activate host defense against pathogens [ 35 , 36 ]. However, excessive induction of DC maturation leads to excessive cytokine secretion, resulting in the stimulation of normal cells, induction of cell apoptosis, and secondary stimulation of immune cells by dead cells, ultimately causing acute or chronic inflammatory diseases [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive induction of DC maturation leads to excessive cytokine secretion, resulting in the stimulation of normal cells, induction of cell apoptosis, and secondary stimulation of immune cells by dead cells, ultimately causing acute or chronic inflammatory diseases [ 37 , 38 , 39 ]. As is evident, DCs play an important role in regulating the host immune response and are used in research aimed at understanding disease pathogenesis or therapeutic mechanisms, in addition to drug development [ 35 , 40 , 41 ]. Interestingly, after inducing maturation of DCs using LPS, and treating these DCs with AYC-EVs, we observed that AYC-EVs inhibited not only LPS-induced phenotypic maturation by inhibiting the expression of surface molecules in DCs, increasing the internalization of extracellular antigens, and suppressing the antigen-presenting ability of DCs, but also the functional maturation of DCs by reducing the expression of pro- and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…DCs are the key players in the recognition and subsequent packaging and presentation of the antigenic molecules to activate the downstream immune effector machinery to produce specific immune response. DCs are generally considered as the interface between the innate and adaptive immune response [50]. Upon interaction and recognition with the bacterial pathogens the DCs leads to the enhanced expression of MHC molecules.…”
Section: Dendritic Cellsmentioning
confidence: 99%